PENGARUH TEKANAN PANAS DAN KEBISINGAN TERHADAP PERUBAHAN TEKANAN DARAH DAN DENYUT NADI PADA PEKERJA TEKSTIL DI PT. X PEKALONGAN - Suparyati . (LPPM Universitas Pekalongan, 2014)
In the workplace, there are several factors which influence the work environment such as :physical factors, chemical factors, biological factors dan psychologi factors. All of these may interfere with the working environment and affect the health and safety. One source of danger of physical environment factors in the workplace is a heat pressure and noise. The heat pressure coming from the roof and engine production, noisy condition is caused there are machines that work indoors can cause physiological disorders that changes in blood pressure and pulse on workers. Aim of this research was to analyze of differential blood pressure and pulse of worker within production spinning yarn Department PT. X Pekalongan both before and after working. This research type was an observational research Cross Sectional approach, research population were 196 persons by 46 person samples. Research result showed that heat pressure and noise within all of work location already exceeded limit threshold value. There were differential blood pressure, between before and after working. The average before working (systole = 119,91 mmHg, diastole =75 mmHg) higher than after worked of systole value (systole = 107,82 mmHg, diastole = 67,39 mmHg) respectively. There were dissimilarity pulse beat before and after working. The average pulse beat before worked (85,15 times/minute) less than after worked (99,15 times/minute). The p value of all experiments above is 0,000. There were no differential blood presussure and pulse beat from all work location based on heat pressure level and noise condition. Keywords: heat pressure, noise, blood pressure, pulse.